AFFECTING FACTORS FOR PARTIAL DISCHARGE INCEPTION VOLTAGE LEVELS IN ELECTRIC MOTORS - Nuorala, Tomi (My University, 2015)
Partial discharge (PD) is a localised dielectric breakdown of a small portion. PDs often start within voids, such as air bubbles in solid resin insulation. PDs can erode solid insulation and eventually lead to breakdown of insulation. PDs can usually be prevented through careful design and material selection. PD prevention is essential to ensure reliable and long-term operation of electric motor. In this thesis partial discharge occurrence is studied. Then stator winding insulation systems and properties of insulation materials, such as laminates, resins and enamels are presented. Also, partial discharge prevention is studied. Finally, relevant parts of IEC 60034 standard family are presented. The objectives of this thesis were to find out how insulation systems perform against PDs when tested according to IEC 60034-18-41 and to resolve how different characteristics affect partial discharge inception voltage (PDIV). A literature survey of examined subjects was performed. Laboratory tests were made to find current partial discharge inception voltage levels of stators from three different sizes and from four different insulation system were tested. Insulation system was broken down on paper and the effect on partial discharge inception voltage of different parts and materials of insulation system was analysed. As a result of this thesis it was found that some insulation systems need improvements to reliably reach IVIC C levels. Some developing targets in insulation system was also discovered.
Keywords: PDIV; electric motor; IEC 60034; insulation; fi=Sähkötekniikka|en=Electrical Engineering|; fi=Sähkö- ja energiatekniikan koulutusohjelma (DI)|